2020
DOI: 10.33309/2639-9164.030205
|View full text |Cite
|
Sign up to set email alerts
|

Can Tranexamic Acid Control Bleeding during and After Total Thyroidectomy? A Randomized Double-blind Clinical Trial Study

Abstract: Introduction: Head and neck operations are among the thyroid surgeries which are occasionally accompanied by blood loss (BL) during operation, tainting the operating field, and increasing the probability of damage to adjacent structures. Several studies have hitherto been conducted toward decreasing the BL that occurs during and after the operation. This study has been designed and executed with the objective of determining and comparing the effectiveness of tranexamic acid (TA) medication on controlling BL du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Alipour et al (2020) 14 showed that the pre-surgery hemoglobin levels were 13.08±1.53 mg/dl in the TXA-receiving group and 13.53±1.44 mg/dl in the control group and considering the obtained P = 0.156, there was no significant difference between the two groups. Furthermore, the post-surgery hemoglobin levels were 12.22±1.42 mg/dl in the TXA-receiving group and 12.52±2.36 mg/dl in the control group which, considering the obtained P = 0.492, were not significantly different.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Alipour et al (2020) 14 showed that the pre-surgery hemoglobin levels were 13.08±1.53 mg/dl in the TXA-receiving group and 13.53±1.44 mg/dl in the control group and considering the obtained P = 0.156, there was no significant difference between the two groups. Furthermore, the post-surgery hemoglobin levels were 12.22±1.42 mg/dl in the TXA-receiving group and 12.52±2.36 mg/dl in the control group which, considering the obtained P = 0.492, were not significantly different.…”
Section: Discussionmentioning
confidence: 94%
“…Alipour et al (2020) 14 aimed to determine and compare the effectiveness of tranexamic acid (TXA) medication on controlling BL during and after total thyroidectomy. They carried out as a double-blind clinical trial on 83 patients affected with benign and malignant pathologies which were candidates for total thyroidectomy surgical operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation